Challenges in promoting learner autonomy in blended learning: perspectives from English as a foreign language teachers in China - Cao, Yongmei; Jeyaraj, Joanna Joseph; Bakar Razali, Abu (Macrothink Institute, 2024)
Blended learning is gaining popularity as a prevailing practice in higher education worldwide. This study explores the challenges faced by experienced English as a Foreign Language teachers in promoting learner autonomy within blended learning environments. Drawing from interviews and classroom observations conducted with five EFL teachers at a private university in China, the study identifies four key challenges: technological, pedagogical, cultural, and institutional. Technological challenges revolve around concerns regarding technical support, internet reliability, and hardware availability, highlighting the need for sturdy technical infrastructure and supportive mechanisms. Pedagogical challenges include designing effective blended learning activities that balance teacher-led instruction with opportunities for student autonomy, emphasizing the importance of scaffolding learning tasks, and providing adequate support for independent learning. Cultural challenges underscore the influence of cultural factors on student attitudes towards autonomy and authority in the classroom, emphasizing the necessity for culturally responsive teaching practices. Institutional challenges highlight barriers stemming from rigid curriculum requirements, limited professional development opportunities, and a lack of administrative support, underscoring the importance of systemic support and organizational change. The findings offer valuable guidance for institutions, administrators, and EFL teachers on how to design more effective blended EFL courses. Limitations and suggestions for future studies such as larger sample size, rigorous data collection method, and longitudinal studies are provided to enhance our understanding of promoting learner autonomy in blended learning environments.